Consensus Minimal Dataset for Pediatric Emergency Medicine in Switzerland. Issue 10 (11th October 2022) - Wismer, Alice C.; Rakic, Milenko; Kuehni, Claudia E.; Jaboyedoff, Manon; Romano, Fabrizio; Kopp, Matthias V.; Brandenberger, Julia; Staubli, Georg; Keitel, Kristina
Abstract : Objectives: Standardized, harmonized data sets generated through routine clinical and administrative documentation can greatly accelerate the generation of evidence to improve patient care. The objective of this study was to define a pediatric emergency medicine (PEM) minimal dataset for Switzerland (Swiss PEM minimal dataset) and to contribute a subspecialty module to a national pediatric data harmonization process (SwissPedData). Methods: We completed a modified Delphi survey, inviting experts from all major Swiss pediatric emergency departments (PEDs). Results: Twelve experts from 10 Swiss PEDs, through 3 Delphi survey rounds and a moderated e-mail discussion, suggested a subspecialty module for PEM to complement the newly developed SwissPedData main common data model (CDM). The PEM subspecialty CDM contains 28 common data elements (CDEs) specific to PEM. Additional CDEs cover PEM-specific admission processes (type of arrival), timestamps (time of death), greater details on investigations and treatments received at the PED, and PEM procedures (eg, procedural sedation). In addition to the 28 CDEs specific to PEM, 43 items from the SwissPedData main CDM were selected to create a Swiss PEM minimal dataset. The final Swiss PEM minimal dataset was similar in scope and content to the registry of the Pediatric Emergency Care Applied Research Network. Conclusions: A practical minimal dataset for PEM in Switzerland was developed through recognized consensus methodology. The Swiss PEM minimal dataset developed by Swiss PEM experts will facilitate international data sharing for PEM research and quality improvement projects.